Ground-state solutions to a Kirchhoff-type transmission problem - Li, Fuyi; Zhang, Ying; Zhu, Xiaoli; Liang, Zhanping (Topological Methods in Nonlinear Analysis, 2020)
In this paper, we consider the existence of ground-state solutions to nonlinear Kirchhoff-type transmission problems by using the methods from (Silvia Cingolani and Tobias Weth, {\it On the planar Schrödinger-Poisson system}, Ann. Inst. H. Poincaré Anal. Non Linéaire {\bf 33} (2016), no.\ 1, 169-197). Here, we avoid the conditions under which the nonlinear terms of $f$ and $g$ are forms of $C^1$. In particular, when $N=2$, the existence of ground-state solutions is established to the Kirchhoff-type transmission problem with exponent-type nonlinearity.